Clinical paired study among patients with idiopathic condylar resorption versus osteoarthritis of temporomandibular joint - Yingjie Xu; Mengying Jia; Bo Shao; Yang Sun; Wei He; Qiaoying Tong; Zhongcheng Gong (Elsevier, 2021)
The idiopathic condylar resorption (ICR) is a kind of disease with severe bone damage to the temporomandibular joint condylar process. ICR high misdiagnosis rate based on the similarities in symptoms and imaging manifestations with temporomandibular joint osteoarthritis (TMJOA). To provide key points for the accurate diagnosis of ICR and TMJOA. Here we show that the number of malocclusion factors and imaging findings in the TMJOA group has significant differences from statistics in the ICR group. We found that the ICR patients might have no oral side function or bad chewing habits without joint noising and mostly with the planar profile of condyle apex and poor subchondral bone continuity after bone resorption. Our results demonstrate key points for a precise diagnosis and differential of ICR and TMJOA. We anticipate our assay to be a theoretical foundation on assisting clinicians in better differentiation against the disease definitely.